Screening and Rapid Identification of Campylobacter Spp. DNA by FlaA PCR Based Method on Chicken and Human Fecal Samples in Egypt - Ramadan , Hazem; Jackson, Charlene; Hinton Jr., Arthur (International Journal of Poultry Science, 2015)
Due to culturability requirements encountered by the conventional isolation of Campylobacter spp., rapid molecular techniques for its direct identification from clinical samples are useful. In this study, Campylobacter spp. DNA from human stool and chicken fecal samples were detected by flagellin gene (flaA) PCR. A total of 297 samples consisting of 163 adult human stools (102 from diarrheic patients and 61 from healthy persons) and 134 chicken feces were subjected to flaA PCR. Ten reference strains of Campylobacter spp. were included in this study as positive controls. Thirteen stool samples (7.98%) from the human fecal samples and 39 chicken fecal samples (29.1%) yielded the genus specific 1.7 Kb amplicon of Campylobacter spp. Eight (7.84%) diarrheic human stool specimens out of 102 samples and 5 (8.2%) apparently healthy human stool specimens out of 61 samples were positive by flaA PCR assay. All the Campyloacter reference strains examined giving the specific amplicon of 1.7 Kb. The existence of Campylobacter spp. DNA detected by flaA PCR in poultry and human samples taken from locations of Egypt highlights the zoonotic potential of Campylobacter. To the best of our knowledge, this is the first report in Egypt that uses flaA PCR as a rapid screening method for the direct detection of Campylobacter spp. from human and chicken feces.